If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -3) = 4x + bx + 9 Reorder the terms: (-3 + 2x) = 4x + bx + 9 Remove parenthesis around (-3 + 2x) -3 + 2x = 4x + bx + 9 Reorder the terms: -3 + 2x = 9 + bx + 4x Solving -3 + 2x = 9 + bx + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1bx' to each side of the equation. -3 + -1bx + 2x = 9 + bx + -1bx + 4x Combine like terms: bx + -1bx = 0 -3 + -1bx + 2x = 9 + 0 + 4x -3 + -1bx + 2x = 9 + 4x Add '-4x' to each side of the equation. -3 + -1bx + 2x + -4x = 9 + 4x + -4x Combine like terms: 2x + -4x = -2x -3 + -1bx + -2x = 9 + 4x + -4x Combine like terms: 4x + -4x = 0 -3 + -1bx + -2x = 9 + 0 -3 + -1bx + -2x = 9 Add '3' to each side of the equation. -3 + -1bx + 3 + -2x = 9 + 3 Reorder the terms: -3 + 3 + -1bx + -2x = 9 + 3 Combine like terms: -3 + 3 = 0 0 + -1bx + -2x = 9 + 3 -1bx + -2x = 9 + 3 Combine like terms: 9 + 3 = 12 -1bx + -2x = 12 Reorder the terms: -12 + -1bx + -2x = 12 + -12 Combine like terms: 12 + -12 = 0 -12 + -1bx + -2x = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(12 + bx + 2x) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(12 + bx + 2x)' equal to zero and attempt to solve: Simplifying 12 + bx + 2x = 0 Solving 12 + bx + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + bx + -12 + 2x = 0 + -12 Reorder the terms: 12 + -12 + bx + 2x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + bx + 2x = 0 + -12 bx + 2x = 0 + -12 Combine like terms: 0 + -12 = -12 bx + 2x = -12 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| (x^2+3)/(x+3)=0 | | y=-1/60x^2+x+66/10 | | ln(2x-5)=1.68 | | C^2-7x=8 | | 15=.5x(2+3) | | (A-2)(a-3)=6 | | X^2+3c-10=0 | | t^2-9t+5=0 | | 0=9(k-0.67)+33 | | 4(w-1)+2(w-2)=4 | | x^2+32*x+4.8=0 | | 0=-16t^2+15t+2 | | 64=42 | | -6b-14+4b=-2 | | -5-15d+1=14d-32 | | 66.5+x=88-29.6 | | -3(2z-7)=18-3z+21-3z | | 0=2x+1-4x+3 | | -7(2x-4)=28 | | (6x^6/2x^4)^-4 | | 27y^2+69y-8=0 | | (X+1)(x-8)+28=3x-1 | | (4x-3)(-5)=75 | | 34p+22p-11p=p+88 | | 5y-7=80-18 | | x^2-mx-12=0 | | X/8+2=5 | | 7x+4x=7 | | -4(2x-1)=-20 | | (x+11)/2=-14 | | -3+x=-4 | | 8x-y-7+14x=0 |